The CIA in Ecuador. - Becker, Marc. (American Encounters/Global Interactions Series, 2021)
Marc Becker draws on recently released US government surveillance documents on the Ecuadorian left to chart social movement organizing efforts during the 1950s, showing how the local patterns and dynamics that shaped the development of the Ecuadorian left could be found throughout Latin American during the cold war.